The future of the humanities in primary schools – reflections in troubled times. Issue 3 (4th May 2017) - Eaude, Tony; Butt, Graham; Catling, Simon; Vass, Peter
ABSTRACT: This article reflects on the implications for practitioners, researchers and policy-makers of the future of the humanities in primary schools in the light of the challenges facing future generations. There is wide divergence in the four jurisdictions of the UK. The humanities are perceived as important, in principle, though curriculum frameworks differ. However, the status of the humanities is often uncertain, in practice, given the current emphasis on outcomes in literacy and numeracy. There is a lack of robust research on how, and by whom, the humanities are taught. The more theoretical articles suggest that the humanities, broadly conceived, are an essential aspect of young children's education – to enable a deeper understanding of human culture and identity, and to develop the qualities and values needed in a diverse world. Additionally, curricular breadth is required alongside a realisation that narrowly focusing on propositional knowledge is limiting. While this has implications for the whole curriculum, History, Geography and Religious Education have key roles in meeting these aims and in engaging and motivating young children. A stronger policy steer is called for, to ensure that schools give more priority to humanities education, with greater investment in professional development in Initial Teacher Education and beyond.